Exchanging Viewpoint Strategy to Improve Students’ Speaking Skills at SD Negeri 1 Jeneponto - sukmawati, Sukmawati (INOPENDAS: Jurnal Ilmiah Kependidikan, 2025)
This study aims to test the effectiveness of the Exchanging Viewpoint strategy in improving students' speaking ability at SD Negeri 1 Jeneponto. The method used was a quasi-experimental design with a nonequivalent control group design, involving two groups: an experimental group and a control group. The sample consisted of 32 students selected through a cluster random sampling technique, with 16 students each in the experimental and control groups. The experimental group was given treatment in the form of learning using the Exchanging Viewpoint strategy, while the control group only received conventional learning. The instruments used included tests and observations. The results of the analysis showed a significant increase in students' speaking ability in the experimental group, with an average pre-test score of 1.84 increasing to 3 in the post-test. In contrast, the control group only experienced an increase from 2.4 to 2.7. This strategy has been proven to encourage students to be more active, confident, and motivated in expressing opinions through discussions and exchanges of views. Thus, the Exchanging Viewpoint strategy is effective in improving students' English speaking skills and is recommended as an alternative interactive learning method in the classroom.